Message for Solidarity: A Japanese Perspective on the Payment for Forest Ecosystem Services Developed over Centuries of History - Ryoko Ishizaki (MDPI AG, 2021)
Payments for ecosystem/environmental services (PES) have emerged internationally as a new environmental conservation concept over the past two decades. By contrast, Japan has a centuries-long history of using various forms of PES. These schemes can be understood as solutions to interregional problems with forest ecosystem services that have been agreed upon and accepted by the society. This paper aims to consider the significance of PES with respect to cooperative relationships by examining historically formed solutions in Japan. The Japanese experience shows that rather than simply being a demonstration of monetary value, PES in upstream forests were a means of communication across regions, expressing interregional solidarity as a core concept. As connections among communities became less visible, the government artificially created solidarity through payments. The payments gradually shifted from having a socioeconomic meaning to having a psychological meaning. The government sought to substantiate the sense of solidarity by making individual users more aware of the meaning of payments. We can find the significance of this type of PES in the fact that payments can be a way to approach the issue of building solidarity by focusing on the function of payments as messengers rather than them merely having an economic value.